Even low levels of anticardiolipin antibodies are associated with pregnancy-related complications: A monocentric cohort study - Matraszek, Veronika Viktoria; Krofta, Ladislav; Hromadnikova, Ilona (Acta obstetricia et gynecologica Scandinavica, 2025)
INTRODUCTION: Moderate and high levels of anticardiolipin antibodies (aCL), especially in the setting of the antiphospholipid syndrome, are associated with adverse obstetric outcomes. However, the clinical relevance of low aCL levels (<40 MPL/GPL units) is still a matter of debate. The aim of the study was to evaluate obstetric outcomes in pregnancies with low immunoglobulin M (IgM) and/or immunoglobulin G (IgG) aCL positivity. The association between low aCL positivity and maternal baseline characteristics was also studied. MATERIAL AND METHODS: The retrospective monocentric cohort study of prospectively collected data involved a total 3047 singleton pregnancies that underwent the first-trimester screening involving an aCL test and delivered on site. Obstetric outcomes were compared between the low-titer aCL group (IgM ≥7 MPL units and <40 MPL units and/or IgG ≥10 GPL units and <40 GPL units) and the aCL negative group (IgM <7 MPL units and IgG <10 GPL units, reference group). In addition, obstetric outcomes were evaluated with regard to the antibody isotype: IgM-positive group (IgM <40 MPL units, IgG negative) and IgG-positive group (IgG <40 GPL units, IgM negative or <40 MPL units). RESULTS: Overall, the occurrence of pregnancy-related complications was significantly higher (27.91% vs. 19.32%, p = 0.034) in the low-titer aCL group. Concerning the antibody isotype, a higher rate of pregnancy-related complications was observed in the IgG-positive group (54.55% vs. 19.32%, p = 0.001), but not in the IgM-positive group (22.43% vs. 19.32%, p = 0.454). The stillbirth rate did not reach statistical significance. Low-titer aCL pregnancies were more frequently of advanced maternal age (p < 0.001), suffered from autoimmune diseases (p < 0.001), chronic hypertension (p = 0.040), and hereditary thrombophilia (p = 0.040). In addition, they had more often a positive history of stillbirth (p < 0.001), underwent conception via assisted reproductive technologies (p < 0.001), were administered low-dose aspirin (p < 0.001), low-molecular-weight heparin (p = 0.018) and immunomodulatory drugs (p < 0.001), and delivered earlier (p = 0.018). CONCLUSIONS: Even low aCL levels are associated with a higher incidence of pregnancy-related complications, but only in the case of IgG antibody isotype presence. Screening for aCL in the first trimester has some prognostic value, but further studies are needed to determine whether its potential implementation into routine clinical practice would improve antenatal care.
Keywords: výsledek těhotenství; Pregnancy; Humans; antifosfolipidový syndrom; imunoglobulin G; kohortové studie; Female; Antibodies, Anticardiolipin; first‐trimester screening; dospělí; anticardiolipin antibodies; Pregnancy Outcome; lidé; Pregnancy Complications; stillbirth; antikardiolipinové protilátky; Antiphospholipid Syndrome; Cohort Studies; Adult; ženské pohlaví; Retrospective Studies; těhotenství; pregnancy‐related complications; komplikace těhotenství; retrospektivní studie; imunoglobulin M; Immunoglobulin G; Immunoglobulin M